Enzymatic/Immunoassay Dual‐Biomarker Sensing Chip: Towards Decentralized Insulin/Glucose Detection. Issue 19 (3rd April 2019) - Vargas, Eva; Teymourian, Hazhir; Tehrani, Farshad; Eksin, Ece; Sánchez‐Tirado, Esther; Warren, Paul; Erdem, Arzum; Dassau, Eyal; Wang, Joseph
Abstract: Performing bioassay formats based on enzyme and antibody recognition reactions with a single detection chip remains an unmet challenge owing to the different requirements of such bioassays. Herein, we describe a dual‐marker biosensor chip, integrating enzyme and antibody‐based assays for simultaneous electrochemical measurements of insulin (I) and glucose (G). Simultaneous G/I sensing has been realized by addressing key fabrication and operational challenges associated with the different assay requirements and surface chemistry. The I immunosensor relies on a peroxidase‐labeled sandwich immunoassay, while G is monitored through reaction with glucose oxidase. The dual diabetes biomarker chip offers selective and reproducible detection of picomolar I and millimolar G concentrations in a single microliter sample droplet within less than 30 min, including direct measurements in whole blood and saliva samples. The resulting integrated enzymatic‐immunoassay biosensor chip opens a new realm in point‐of‐care multiplexed biomarker detection. Abstract : A dual‐marker biosensor chip integrating enzyme and antibody‐based assays for simultaneous electrochemical measurements of insulin (I) and glucose (G) is presented. Simultaneous G/I sensing has been realized by addressing key fabrication and operational challenges associated with the different assay requirements and surface chemistry.